Tipos de mulch en el rendimiento de Lactuca sativa l. lechuga variedad great lakes, Zungarococha-Loreto.2022 - Rojas Diaz, Alfredo Junior (2023)
his research evaluated the effect of different types of mulch on lettuce yield in the Loreto region. Four types of mulch were evaluated: guava litter, ficus litter, sawdust and a treatment without mulch. Variables such as height, width, number of leaves, leaf weight, stem weight, and lettuce plant weight were measured. The results indicated that there was no significant difference in lettuce height, width, number of leaves and stem weight between the different types of mulch. However, there was a slight difference in leaf weight and lettuce plant weight, with guava mulch producing the highest average weight. Despite this, the ANOVA statistical test did not find significant differences between the different types of mulch. Based on these findings, the use of mulch in lettuce production in the Loreto region is recommended, since it can improve soil quality, reduce water evaporation, and control weeds. The use of guava litter is suggested as the most effective type of mulch in improving leaf weight and lettuce plant weight, although it should be noted that the effects of mulch may vary depending on local conditions.